Towards Profiles of Resistance Development and Toxicity for the Small Cationic Hexapeptide RWRWRW-NH2 - Wenzel, Michaela; Prochnow, Pascal; Mowbray, Catherine; Vuong, Cuong; Höxtermann, Stefan; Stepanek, Jennifer J.; Albada, H. Bauke; Hall, Judith; Metzler-Nolte, Nils; Bandow, Julia E. (Frontiers in Cell and Developmental Biology, 2016)
RWRWRW-NH2 (MP196) is an amphipathic hexapeptide that targets the bacterial cytoplasmic membrane and inhibits cellular respiration and cell wall synthesis. In previous studies it showed promising activity against Gram-positive bacteria and no significant cytotoxicity or hemolysis. MP196 is therefore used as lead structure for developing more potent antibiotic derivatives. Here we present a more comprehensive study on the parent peptide MP196 with regard to clinically relevant parameters. We found that MP196 acts rapidly bactericidal killing 97% of initial CFU within 10 minutes at two times MIC. We were unable to detect resistance in standard 24 and 48 h resistance frequency assays. However, MP196 was effective against some but not all MRSA and VISA strains. Serum binding of MP196 was intermediate and we confirmed its low toxicity against mammalian cell lines. MP196 did neither induce NFκB activation nor cause an increase in IL8 levels at 250 μg/mL, and no IgE-dependent activation of basophil granulocytes was detected at 500 μg/mL. Yet, MP196 demonstrated acute toxicity in mice upon injection into the blood stream. Phase contrast microscopy of mouse blood treated with MP196 revealed a shrinking of erythrocytes at 250 µg/mL and severe morphological changes and lysis of erythrocytes at 500 µg/mL. These data suggest that MP196 derivatization directed at further lowering hemolysis could be instrumental in overcoming acute toxicity. The assessment of hemolysis is a critical step in the evaluation of the clinical potential of promising antimicrobial peptides and should be accompanied by microscopy-based morphological analysis of blood cells.